DESIGN AND IMPLEMENTATION SEARCH ENGINE USING METHOD VSM (Vector Space Model) - Khotibul Umam; Yudha Dwi Putra Negara (International Journal of Science, Engineering, and Information Technology, 2022)
Along with the rapid increase in the amount of information on the internet, many internet visitors feel confused in getting information about notebooks available online on the internet. Therefore, it is necessary to compile or organize information about notebooks from several web addresses that contain information about brands, specifications, prices of notebooks, so that it can make it easier for visitors to carry out the process of searching for information about brands, specifications, notebook prices and get information that is in accordance with visitor wishes. A special search engine is an application that functions to find specific information based on keywords entered by visitors. This search engine will be able to provide information about brands, specifications and prices of notebooks easily and quickly. In the process of working this search engine, later all the information on the internet site will be extracted and then stored in a database. then displayed to visitors. Making this final project produces a special search engine application that helps visitors get information about brands, specifications, and prices of notebooks from several webs that are determined directly. From several experimental results, importing brand keywords, specifications and notebook prices in the search engine resulted in 80% precision and 94% recall.